Perlindungan Hukum Terhadap Konsumen Terkait Dengan Iklan Produk Kecantikan Yang Tergolong Mengelabui Konsumen - Manggala, Ferdiansyah Putra; Santyaningtyas, Ayu Citra (WELFARE STATE Jurnal Hukum, 2025)
The development of the world, which includes the world of communication and information, encourages the development of a perspective of human needs. This need encourages development in the business world, especially the world of marketing through advertising media. With the encouragement in the business world and the many public demands for their needs, it encourages companies to get as much profit as possible in the goods and/or services sector. The development of the need for tertiary needs has now shifted to primary needs, as well as beauty products. Beauty product companies in terms of making as much profit as possible can do anything, one of which is by encouraging marketing, in this case beauty product advertisements that seem exaggerated and give unilateral claims that the products provided are the best products in their field even though it is not uncommon for the information provided in the advertisement to seem inconsistent and contain uncertain promises in the advertisement. Therefore, the urgency of research on advertisements that are classified as deceiving consumers, in this case beauty product advertisements that deceive consumers, is considered necessary in providing insight and knowledge to the general public.